Non‐linear, cata‐Condensed, Polycyclic Aromatic Hydrocarbon Materials: A Generic Approach and Physical Properties. Issue 28 (8th June 2015) - Haire, Barnaby T.; Heard, Kane W. J.; Little, Mark S.; Parry, Adam V. S.; Raftery, James; Quayle, Peter; Yeates, Stephen G.
Abstract A generic approach to the regiospecific synthesis of halogenated polycyclic aromatics is made possible by the one‐ or two‐directional benzannulation reactions of readily available (ortho‐allylaryl)trichloroacetates (the "BHQ" reaction). Palladium‐catalysed cross‐coupling reactions of the so‐formed haloaromatics enable the synthesis of functionalised polycyclic aromatic hydrocarbons (PAHs) with surgical precision. Overall, this new methodology enables the facile mining of chemical space in search of new electronic functional materials.